Aetiology and Severity of Diarrhoea among Children Under Five in Uvwie Local Government Area, Delta State, Nigeria - Onojafe, Joseph Oghenebukome; Onoriasakpobare, Felix Omamuyovwe; Ugegeh, Desmond Oghanihun (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
In children under five, diarrhea is a prevalent health issue that causes avoidable morbidity and mortality worldwide. Unclean water and inadequate sanitation have long been linked to diarrhea. Given the government's and advocates' policies about cleanliness and health care, our goal is to assess the causes and severity of diarrhea in children under five in both urban and rural areas of the Uvwie Local Government Area. A systematic questionnaire was used to gather data from mothers of children under five who visited the Primary Health Care Centers in Alaka, Sedco, Ogbomoro, and Ohore. Based on a nearly equal distribution of 180 youngsters polled between February and June 2022, the findings were presented.Given that 67 children were surveyed during the study period, the findings demonstrated that diarrhea remains a significant health concern. In terms of mothers' educational attainment, 36.1% were illiterate, 31.7% had only completed primary school, 23.3% had completed secondary school, and 8.9% had completed higher education. The majority of moms (51.7%) worked for themselves, and many (42.8%) had low monthly incomes and limited access to pipe-borne water; in contrast, urban areas had better access than rural ones. Public health issues with open defecation remain serious. On the other hand, the chi-square test revealed no significant (>0.05) correlation between the communities' diarrheal incidence and the sort of water sources available.However, based on analysis using the Cohen's d Effect size, it seemed that rural communities had a larger average number of diarrhea cases (19.0) than urban communities (14.5). The effectiveness of food and water supplies, cleanliness, environmental sanitation practices, and health care delivery are all indirectly correlated with the occurrence of diarrhea.